Market discipline during crisis: Evidence from bank depositors in transition countries - Iftekhar Hasan; Krzysztof Jackowicz; Oskar Kowalewski; Łukasz Kozłowski (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
The Central European banking industry is dominated by foreign-owned banks. During the recent crisis, for the first time since the transition, foreign parent companies were frequently in a worse financial condition than their subsidiaries. This situation created a unique opportunity to study new aspects of market discipline exercised by non-financial depositors. Using a comprehensive data set, we find that the recent crisis did not change the sensitivity of deposit growth rates to accounting risk measures. We establish that depositors' actions were more strongly influenced by negative press rumors concerning parent companies than by fundamentals. The impact of rumors was especially perceptible when rumors turned out ex post to be founded. Additionally, we document that public aid announcements were primarily interpreted by depositors as confirmation of a parent company's financial distress. Our results, indicating that depositors react rationally to sources of information other than financial statements, have policy implications, as depositor discipline is usually the only viable and universal source of market discipline for banks in emerging economies.
URN:NBN:fi:bof-201408072111
Keywords: G21; G28; 330; depositor behavior; market discipline; crisis; emerging markets; market rumors